2014
DOI: 10.1021/jz500260s
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Spectra of Dissolved Polysulfides in Lithium–Sulfur Batteries from First-Principles

Abstract: The X-ray absorption spectra (XAS) of lithium polysulfides (Li2Sx) of various chain lengths (x) dissolved in a model solvent are obtained from first-principles calculations. The spectra exhibit two main absorption features near the sulfur K-edge, which are unambiguously interpreted as a pre-edge near 2471 eV due to the terminal sulfur atoms at either end of the linear polysulfide dianions and a main-edge near 2473 eV due to the (x - 2) internal atoms in the chain, except in the case of Li2S2, which only has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
219
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(234 citation statements)
references
References 36 publications
15
219
0
Order By: Relevance
“…Although we also attempted to synthesize Li 2 S 4 powder, it could not be isolated, because it is thermodynamically unstable. 27,40 Since the XANES features of Na 2 S 4 (27,28) are similar to the predicted features of lithium polysulfides, 29 it is a suitable reference for a qualitative analysis.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Although we also attempted to synthesize Li 2 S 4 powder, it could not be isolated, because it is thermodynamically unstable. 27,40 Since the XANES features of Na 2 S 4 (27,28) are similar to the predicted features of lithium polysulfides, 29 it is a suitable reference for a qualitative analysis.…”
Section: Methodsmentioning
confidence: 85%
“…Although the spectra of other polysulfides such as S 3 2− , S 5 2− , S 6 2− , S 8 2− are not presented in this study, the positions of their XANES features are expected to be well represented by the spectrum of S 4 2− polysulfide. [27][28][29] This is rationalized by a computational study, which has demonstrated that the charge on a polysulfide chain migrates toward the two terminal sulfur atoms. 29 This phenomenon leads to a sulfur K-edge XANES signal consisting of two features, with the first feature at ∼2470-1 eV corresponding to the negatively charged terminal sulfur atoms and the second feature at ∼2472-3 eV corresponding to the uncharged ('neutral') internal sulfur atoms.…”
Section: Validation Of Operando Characterization Of Intermediates-mentioning
confidence: 97%
“…Early theoretical work predicted slight variations in the position of the lithium polysulfide pre-edge peak in the adsorption spectra. 23 By using Resonant Inelastic X-ray Scattering (RIXS) no shifts were observed for the set of reference samples, neither within operando measurement. 24 Nevertheless, information gathered from operando XAS measurements can serve as a reliable indicator of changes within the Li-S battery upon operation.…”
mentioning
confidence: 99%
“…As shown in Figure 2c, eq 5 predicts the free energy of sulfur encapsulated in various sized nanopores, as well as at the graphene interface, to within 3% of the values calculated from MD simulations over the entire liquid temperature range ( Figure S6). As with our previous efforts, 34,35 we aim to uncover electronic structure changes upon sulfur impregnation into microporous carbon that can be exploited to both resolve the underlying physical morphologies and reveal molecular scale details of function. A previous study demonstrated that surface molecules at metal interfaces have unique electronic structure, manifested as modulations of their X-ray absorption spectra (XAS).…”
mentioning
confidence: 99%